Integrating RegTech solutions for industry 4.0 - Gopalakrishnan, Badri Narayanan; Gupta, Smita; Gupta, Swati (IGI Global, 2024)
Regulatory compliance and risk management pose significant challenges in today's rapidly evolving financial landscape. Integrating Industry 4.0 technologies such as automation, AI, and machine learning has added complexity to these challenges. Financial institutions need help to keep pace with regulatory changes and technological advancements, leading to inefficiencies and increased compliance costs. Integrating RegTech Solutions for Industry 4.0 provides a comprehensive solution to this problem by offering insights into how regtech can help financial institutions navigate these challenges effectively.Through a series of case studies, this book demonstrates how leading financial institutions have successfully implemented regtech solutions to streamline compliance processes and manage risks efficiently. By showcasing real-world applications, the book offers practical strategies and best practices for integrating regtech into financial operations. Furthermore, the book explores the regulatory implications of Industry 4.0 technologies, such as IoT and blockchain, providing readers with a holistic view of the regulatory landscape.